Nurses’ performance in the face of oncological emergencies: An integrative review - Oliveira, Daniela Costa Salheb de; Lobo, Fausto Ferreira; Vieira, Gabrielle Palheta; Lima, Mariana Souza de; filho, Paulo Monteiro dos Santos; Junior, Neiva José da Luz Dias (Seven Editora, 2023)
Objective: to identify, in the scientific production, the role of nurses in the face of oncological emergencies. Method: Descriptive study, qualitative approach, of the Integrative Literature Review type. PubMed/Medline, LILACS, SciELO, CINAHL, Google Scholar and Web of Science were used as a database and library. For the categorization and lexical analysis of the selected data, the software IRaMuTeQ was used. Results: The formation of 5 correlated classes emerged. There was a limited amount of materials aimed at nursing care, with a small number of articles published in the last 5 years. Conclusion: The role of nurses in oncological emergencies, supported by scientific knowledge, makes a significant difference in the early detection of oncological emergencies, preventing complications and improving quality of life. The limitations of this review refer to the scarcity of current studies that address the role of nurses in oncological emergencies. DOI:https://doi.org/10.56238/globalhealthprespesc-043